Genome and transcriptome wide association study identify candidate genes regulating folate levels in maize - Zou, Chenglin; Yang, Meng; Huang, Aihua; Mo, Runxiu; Zhai, Ruining; Huang, Kaijian (Frontiers in Plant Science, 2025)
BackgroundMaize (Zea mays L.) serves as a crucial dietary source of folate for humans. However, the genetic regulatory mechanisms underlying the natural variation of folate in maize remain poorly understood. Here, we integrated multi-omics approaches to elucidate the molecular mechanisms governing folate accumulation in maize.MethodsA total of 380 maize kernels representing 190 maize inbred lines from China, Thailand, Mexico, and Peru were collected. RNA-seq was conducted on 380 maize kernel samples, and folate content was quantified using high-performance liquid chromatography (HPLC). The samples were stratified into high and low folate groups based on median folate values. Differentially expressed genes (DEGs) were identified between the two groups identified. Candidate genes associated with folate accumulation were further located by integrating transcriptome-wide association studies (TWAS) and genome-wide association studies (GWAS) analyses. Finally, quantitative real-time PCR (qRT-PCR) was employed to validate the expression patterns of these candidate genes.ResultsA total of 137 DEGs that exhibited significant differences between the high-folate and low-folate groups were identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses revealed that these genes were significantly enriched in pathways related to phenylpropanoid biosynthesis, oxidoreductase activity, and stress response. GWAS identified 2,153 candidate genes associated with folate traits (P ≤ 1.00E-05). Through the integration of DEGs and the intersection of genes identified by GWAS, seven candidate genes were further identified. In addition, TWAS analysis further identified 13 causal genes associated with the candidate genes, which are involved in folate biosynthesis. In addition, the expression levels of these candidate genes were validated by qRT-PCR experiments, suggesting significantly higher expressions in the high folate group compared to the low-folate group.ConclusionThis study identifies key regulatory genes potentially influencing folate accumulation in maize and provides critical insights for the development of biofortified maize varieties with enhanced nutritional value.